2006
DOI: 10.4161/psb.1.4.3106
|View full text |Cite
|
Sign up to set email alerts
|

Development of Erect Leaves in a Modern Maize Hybrid is Associated with Reduced Responsiveness to Auxin and Light of Young Seedlings in vitro

Abstract: Modern corn (Zea mays L.) varieties have been selected for their ability to maintain productivity in dense plantings. We have tested the possibility that the physiological consequence of the selection involves changes in responsiveness to light and auxin.Etiolated seedlings of two older corn hybrids 307 and 3306 elongated significantly more than seedlings of a modern corn hybrid 3394. The level of endogenous auxin and activity of PAT in 307 and 3394 were similar. Hybrid 3394 shows resistance to auxinand light-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Some hybrids yield more as plant density is increased while others exhibit no increase or even yield loss (Duvick and Cassman, 1999;Grassini et al, 2011;Hashemi et al, 2005;Monneveux et al, 2005). Plant density tolerance likely involves multiple factors from categories of traits involving photosynthetic capacity, source-sink relationship, hormonal balance, and plant architecture (e.g., Huang et al, 2009;Collins et al, 2008;Johnson, 2008;Ramon and Rolland, 2007;Fellner et al, 2006;Sawers et al, 2005;Fellner et al, 2003;Smith and Whitelam, 1997;Lambert and Johnson, 1978). We assumed that a combination of traits, likely from diverse categories, may be necessary for expression of PDT.…”
Section: Survey Of Plant Density Tolerance In Us Maize Germplasmmentioning
confidence: 99%
“…Some hybrids yield more as plant density is increased while others exhibit no increase or even yield loss (Duvick and Cassman, 1999;Grassini et al, 2011;Hashemi et al, 2005;Monneveux et al, 2005). Plant density tolerance likely involves multiple factors from categories of traits involving photosynthetic capacity, source-sink relationship, hormonal balance, and plant architecture (e.g., Huang et al, 2009;Collins et al, 2008;Johnson, 2008;Ramon and Rolland, 2007;Fellner et al, 2006;Sawers et al, 2005;Fellner et al, 2003;Smith and Whitelam, 1997;Lambert and Johnson, 1978). We assumed that a combination of traits, likely from diverse categories, may be necessary for expression of PDT.…”
Section: Survey Of Plant Density Tolerance In Us Maize Germplasmmentioning
confidence: 99%
“…In intact seedlings and on a longer time scale, exogenous auxin (native or synthetic) often reduces the elongation of various plant organs (Boerjan et al 1995;King et al 1995;Thomine et al 1997;Fellner et al 2003Fellner et al , 2006. In Arabidopsis, we similarly observed that as in the case of boron, auxin-induced inhibition of hypocotyl growth is affected by blue light BL (Fellner, unpublished results).…”
Section: Introductionmentioning
confidence: 62%
“…We previously reported that in comparison with old maize hybrid 307, expression of ABP4 in etiolated mesocotyls is strongly reduced in the modern hybrid 3394 (Fellner et al 2006). Moreover, in the old hybrid 307, but not in the modern hybrid 3394, the sensitivity of mesocotyl to exogenous auxin increased with the elevation of the calcium concentration in the growth medium ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 90%